Financial security in retirement: the importance of savings vs earnings in Malaysia - Krishnaveni, Vilayudhan; Md Jusoh, Zuroni; Othman, Mohd Amim; Zainudin, Norzalina (Human Resource Management Academic Research Society, 2024)
This manuscript delves into the intricate relationship between income and wealth retention in Malaysia’s evolving economic landscape. It begins with an overview of life expectancy trends, emphasizing demographic shifts and economic challenges shaping financial planning. Individuals can establish a robust financial foundation by cultivating financial acumen— focusing on saving and strategic investments. This foundation shields them against unexpected setbacks and facilitates long-term wealth growth and goal attainment. Unfortunately, such planning remains voluntary and underutilized in countries like Malaysia. Financial literacy is pivotal in adequate retirement preparation, ensuring financial independence and a higher quality of life amid rising living costs and inadequate savings. Recent reforms, including raising the default retirement savings threshold and promoting annuity-based withdrawals, aim to enhance retirement security. However, diversification of post-retirement financial resources remains essential to mitigate the impact of inflation and maintain purchasing power. Social dynamics—such as family influence, peer interactions, and advice from financial experts—shape investment intentions. nce, peer interactions, and advice from financial experts—shape investment intentions. Moreover, future orientation is a crucial compass in personal finance, guiding individuals to align their current decisions with long-term goals. This manuscript provides valuable insights into wealth management dynamics, emphasizing that retaining wealth is as crucial as earning it.